2022
DOI: 10.1002/mds.28932
|View full text |Cite
|
Sign up to set email alerts
|

GBA and APOE Impact Cognitive Decline in Parkinson's Disease: A 10‐Year Population‐Based Study

Abstract: Background Common genetic variance in apolipoprotein E (APOE), β‐glucocerebrosidase (GBA), microtubule‐associated protein tau (MAPT), and α‐synuclein (SNCA) has been linked to cognitive decline in Parkinson's disease (PD), although studies have yielded mixed results. Objectives To evaluate the effect of genetic variants in APOE, GBA, MAPT, and SNCA on cognitive decline and risk of dementia in a pooled analysis of six longitudinal, non‐selective, population‐based cohorts of newly diagnosed PD patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 65 publications
2
53
1
Order By: Relevance
“…Two of the cohorts (TPD and OPDC) recruited individuals of similar age to incident cohorts of Northern European ancestry, namely the cohorts included in the Parkinson's Incidence Cohorts Collaboration. 95 However, the remaining cohorts have a mean younger age than the observed average in incident population-based cohorts, which suggests these cohorts might not be representative of the wider PD population. Given these are non-incident cohorts, it is not possible to know when individuals who met criteria for dementia at baseline developed PDD, and so these were excluded from further analysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Two of the cohorts (TPD and OPDC) recruited individuals of similar age to incident cohorts of Northern European ancestry, namely the cohorts included in the Parkinson's Incidence Cohorts Collaboration. 95 However, the remaining cohorts have a mean younger age than the observed average in incident population-based cohorts, which suggests these cohorts might not be representative of the wider PD population. Given these are non-incident cohorts, it is not possible to know when individuals who met criteria for dementia at baseline developed PDD, and so these were excluded from further analysis.…”
Section: Discussionmentioning
confidence: 96%
“…It is nevertheless reassuring that our study has identified some of the same genetic factors associated with higher risk of progression to dementia as large, incident population-based cohorts with long follow-up times such as APOE ε4 and GBA mutations, despite the potential limitations of large non-incident longitudinal cohorts. 95 …”
Section: Discussionmentioning
confidence: 99%
“…Our study has limitations that offer opportunities for further research. First, the age at diagnosis of our cohort (ie, 64 years) was lower than that commonly reported for the international PD consortiums (eg, 71 years for the Parkinson's Incidence Cohorts Collaboration) 81 ; this may limit the generalization of our findings and prompt future studies to replicate our results in a more representative study sample. Second, the relatively small sample size did not allow to test the stability of the clustering results by dataset split and to evaluate the contribution of other explanatory variables (eg, mood disorders or sleep disorders) possibly influencing memory functioning.…”
Section: Discussionmentioning
confidence: 70%
“…25 In PD, carriers of the APOE-ε4 allele were found to have both quicker cognitive decline compared with noncarriers and an increased risk of progression to dementia. 26 Prior studies have found rs9877502 on the 3q28 locus between GEMC1 and OSTN to be associated with higher CSF tau levels and identified a risk variant (rs1316356) for AD that is in linkage disequilibrium with this SNP. 4,5 In addition, GEMC1 has been recently reported to be a key molecule in multiciliated cell differentiation.…”
Section: Discussionmentioning
confidence: 99%